If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5b + 4 = 6b + -4 Reorder the terms: 4 + 5b = 6b + -4 Reorder the terms: 4 + 5b = -4 + 6b Solving 4 + 5b = -4 + 6b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-6b' to each side of the equation. 4 + 5b + -6b = -4 + 6b + -6b Combine like terms: 5b + -6b = -1b 4 + -1b = -4 + 6b + -6b Combine like terms: 6b + -6b = 0 4 + -1b = -4 + 0 4 + -1b = -4 Add '-4' to each side of the equation. 4 + -4 + -1b = -4 + -4 Combine like terms: 4 + -4 = 0 0 + -1b = -4 + -4 -1b = -4 + -4 Combine like terms: -4 + -4 = -8 -1b = -8 Divide each side by '-1'. b = 8 Simplifying b = 8
| 3-6x=4x+0 | | 4(2x)=100 | | 42x-45=-72 | | 5x-1+9x=4x-7 | | (6+3x)=x-18 | | 6n+4=28-11 | | 4w^2+12w+9=1169 | | x^2-6x+9=64 | | y+6x=3 | | 7x+3y-8=4 | | 20w^2-31w+12=0 | | 16a^2-70a+49=0 | | 1x+2=-6 | | -4x^2=9x | | 5a+3(216+a)=888 | | 4y-7-6y-2= | | -2-2(-7x+7)=82 | | -15=-12+3r | | -7(1k-8)+2k= | | 2.5x+4=6x+4 | | 5x+5=6x+2 | | (c+3)(c+4)=2 | | 7x+3=-2x+21 | | Mp+mz=r | | lnx^7-10lnx=1 | | 3+2*[(2+1)*5+8]= | | -5x+2=-2x-31 | | 2y+6+8y+10+y+32=180 | | X^2+13x-64=0 | | 5m-28=-33+6m | | 3x^2+56=-136 | | 9n-23=17+n |